(untitled) (Fiep Bulletin - online, 2015)
This article was conducted through literature and field research, where the prior informed consent of students to the questionnaire prepared by the applicator with closed questions to students in a class of 8th grade of elementary school occurred in the city of Foz do Iguaçu Pr , totaling 27 students, aged 13-15 years. We sought to understand factors that influence the profile of the fans, which in turn, demonstrate attitudes and behaviors articulated by psychological, cultural, and economic elements, their relationships with the global society. According to the research, the work shows in summary, that the violence produced by groups of fans is prevalent in football, being part of the everyday dimension of mostly large urban centers, in contemporary Brazilian society as a result of " emptying the political " cultural and collective new social subjects. The different attitudes and behaviors, represented by different elements that form the profile of social groups, which often compare themselves as tribes, with symbols and similarities that differentiate between them by setting aggressive degrees due to rivalries between them, can lead to social environments common and can be avoided. In this way, professional football for example, can be one of the joints between the urbanization process for the organized supporters who bring and determine how often gangs present in Brazilian football, reflecting mostly in global contexts. And the behavioral problems are linked to the person’s education , particularly the plan to build a linked awareness culture directly between humans.